16/9×2/5+2/5+20/9×2/5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: =1/8*9/4=9/32
2: =8/27*243/32=9/4
3: =(5/4*4/5)^5*(4/5)^2=16/25
4: \(=\left(-\dfrac{5}{6}\cdot\dfrac{6}{5}\right)^2\cdot\left(\dfrac{6}{5}\right)^2=\dfrac{36}{25}\)
5: \(=\left(-\dfrac{4}{3}\right)^3\cdot\left(\dfrac{3}{4}\right)^{10}=\left(-1\right)\left(\dfrac{3}{4}\right)^7=-\left(\dfrac{3}{4}\right)^7\)
6: \(=\left(\dfrac{1}{3}\cdot\dfrac{-9}{2}\right)^4\left(-\dfrac{9}{2}\right)^2=\left(-\dfrac{3}{2}\right)^4\cdot\dfrac{81}{4}=\dfrac{9}{4}\cdot\dfrac{81}{4}=\dfrac{729}{16}\)
8: =(0,2*5)^4*5^2=25
10: =-0,5^5*2^10
=-0,5^5*2^5*2^5
=-32
13: =(0,5*2)^2*2^2=4
Sai ở chỗ:<=> 4-9/2 = 5-9/2 <=> 4=5
thế này mới đúng!
\(\left(4-\frac{9}{2}\right)^2=\left(5-\frac{9}{2}\right)^2\Leftrightarrow\left(4-\frac{9}{2}\right)\left(4-\frac{9}{2}\right)=\left(5-\frac{9}{2}\right)\left(5-\frac{9}{2}\right)\)
f: \(-20:2^2+\left(-5\right)^9:5^8\)
\(=-20:4-5^9:5^8\)
=-5-5
=-10
g: \(-100:5^2+\left(-7\right)\cdot\left(-3\right)^2\)
\(=-\dfrac{100}{25}-7\cdot9\)
=-4-63
=-67
h: \(-84:4+3^9:\left(-3\right)^7+\left(-5\right)^0\)
\(=-21-3^9:3^7+1\)
\(=-21-3^2+1\)
=-20-9
=-29
i: \(-29-\left[16+3\left(51-49\right)\right]\)
\(=-29-16-3\cdot2\)
=-45-6
=-51
j: \(-58\cdot75+58\cdot\left(-50\right)-58\left(-25\right)\)
\(=58\cdot\left(-75\right)+58\left(-50\right)+58\cdot25\)
\(=58\left(-75-50+25\right)\)
\(=-58\cdot100=-5800\)
a) Ta có: \(\dfrac{-5}{7}\left(\dfrac{14}{5}-\dfrac{7}{10}\right):\left|-\dfrac{2}{3}\right|-\dfrac{3}{4}\left(\dfrac{8}{9}+\dfrac{16}{3}\right)+\dfrac{10}{3}\left(\dfrac{1}{3}+\dfrac{1}{5}\right)\)
\(=\dfrac{-5}{7}\cdot\dfrac{3}{2}\cdot\dfrac{21}{10}-\dfrac{3}{4}\cdot\dfrac{56}{3}+\dfrac{10}{3}\cdot\dfrac{8}{15}\)
\(=\dfrac{-9}{4}-14+\dfrac{16}{9}\)
\(=\dfrac{-1621}{126}\)
b) Ta có: \(\dfrac{17}{-26}\cdot\left(\dfrac{1}{6}-\dfrac{5}{3}\right):\dfrac{17}{13}-\dfrac{20}{3}\left(\dfrac{2}{5}-\dfrac{1}{4}\right)+\dfrac{2}{3}\left(\dfrac{6}{5}-\dfrac{9}{2}\right)\)
\(=\dfrac{-17}{26}\cdot\dfrac{13}{17}\cdot\dfrac{-3}{2}-\dfrac{20}{3}\cdot\dfrac{3}{20}+\dfrac{2}{3}\cdot\dfrac{-33}{10}\)
\(=\dfrac{3}{4}-1-\dfrac{11}{5}\)
\(=-\dfrac{49}{20}\)
`16/9xx2/5+2/5+20/9xx2/5`
`=2/5xx(16/9+1+20/9)`
`=2/5xx5`
`=2`
chịu chịu